A cross sectional study of indications and complications of primary cesarean section at District Hospital Patiala - Phool, Divya; Pandove, Aarti; Aggarwal, Ramita; Salunke, Shital (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Caesarean section is one of the major oldest surgical procedure that has been performed all over world to save life of mother and fetus. The steadily increasing global rates of caesarean section have become one of the most debated topics in maternity care, as its prevalence has increased alarmingly in recent years. The aim is to assess the indications and complications of primary caesarean section in primigravida and multigravida. Methods: A cross sectional study carried out over a period of 1 year from April 2022 to March 2023, among 300 pregnant women from labour room in Mata Kaushalya District Hospital, Patiala by simple random sampling method. Results: Majority 54.7% of cesarean section were of primigravida and 45.3% were of multigravida. Maximum number of caesareans was between 26-30 yrs of age group. 68% women underwent emergency caesarean section and 32% underwent elective caesarean section. 6% underwent caesarean section at <37 weeks gestational age, maximum 83%caesarean section were at 37- 40 weeks gestational age and 11% caesarean section were at >40 weeks gestational age. Among primigravida, majority 35%were fetal distress, 24.29% CPD, malpresentation and malposition were 6.77%, 5.08% NPOL, 3.38% were placenta previa, 2.25% were IUGR, 3/177 (1.69%), severe oligohydroamnios 1.69%, preeclampsia and 1/177 (0.56%) were abruptio placenta. Among multigravida women 41.46% had most common indication was fetal distress, 2.43% had non progress of labour, 14.63% had malpresentations and malpositions. Conclusions: The proportion of primigravida undergoing primary Caesarean delivery was much more than multigravida. However, complications related to primary CS was much higher in multigravida.